Seasonal and Spatial Variation of Water Quality Index of Bassi Tehsil of District Jaipur, Rajasthan, India (Global Journal of Science Frontier Research, 2016)
The present study was intended to calculate the water quality index (WQI) of Bassi Tehsil of district Jaipur, Rajasthan, India in order to assess its suitability for drinking purpose. For this ground water samples from 71 sampling sites of 50 villages of study area were collected from tube wells and hand pumps of varying depths in pre and post monsoon seasons and analyzed for ten physico-chemical parameters namely pH, Total Alkalinity, Total Hardness, Calcium, Magnesium, Chloride, Nitrate, Fluoride, Total Dissolved Solid and Electrical Conductivity. Analysis of results showed that almost all parameters were exceeding the permissible limits prescribed by BIS, ICMR and WHO. Assessment of water quality index (WQI) showed remarkable variation of water quality as WQI values ranged from 13.53 to 1052.2 in premonsoon and 25.72 to 1024.6 in post monsoon season. The study also revealed that drinking water of Bassi tehsil is not potable and there is an instant need to take ameliorative steps in this region to prevent the population from adverse health effects as 61.97% and 63.38% ground water samples were classified under "unsuitable for drinking" category in accordance with their WQI values in pre and post monsoon seasons, respectively.
Keywords: groundwater quality; physico-chemical parameters; water quality index; bassi tehsil and rajasthan